Assessment of Hammer Energy Measurement for the Standard Penetration Test (SPT) Using Pile Driving Analyzer and Kallpa Analyzer Devices in Peru - Ortiz, Carmen (2025)
Energy measurement in dynamic penetration tests is key to correctly interpreting test results and ensuring comparable geotechnical data. Although commercial devices are widely used, their high cost limits adoption in developing regions such as Peru, affecting the accuracy of soil evaluation in many geotechnical studies. In this context, this research presents an energy measurement system called Kallpa, which uses low-cost electronic components to digitize sensor signals during Standard Penetration Tests (SPTs). Kallpa employs high-resolution analog-to-digital converters (ADCs) with an advanced sampling frequency, processing and storing data via a Raspberry Pi 4 microcomputer. The sensors, including accelerometers and strain gauges, were calibrated and compared with the Pile Driving Analyzer (PDA) to validate their accuracy in the Kallpa system. This study involved sixteen Standard Penetration Tests (SPTs) conducted in various regions of Peru using donut hammers and two tests involving automatic hammers. The results demonstrate that the Kallpa system is comparable to other energy measurement devices on the market, such as the Dynamic Penetration Test (DPT), which provides accurate SPT energy measurements. The Kallpa Processor (Version 1.0) software was developed to perform data acquisition and calibration, analyzing approximately 500 hammer blows and comparing peak values with those of the Pile Driving Analyzer. The data collected by Kallpa’s sensors strongly agreed with the PDA data, validating the reliability of the device. The Energy Transfer Ratio (ETR) for manual hammers ranged from 43.5% to 68.4%, with an average of 58.9%, whereas automatic hammers presented ETR values between 82% and 87%. The correction of the N60 blow count allowed for the estimation of the relative density of soils evaluated at different depths and locations across Peru.